Sailing to the Afterlife - Ómar Valur Jónasson 1992- (2018)
This paper compares Viking Age boat-burials in Iceland and Scotland. The aim is to show whether the custom can be considered the same in both regions, or whether each has its own characteristics. The basic issue of identifying boat-burials is dealt with. A total of seventeen sites are considered in the analysis, that is, ten in Iceland and seven in Scotland. However, only fifteen were found to provide enough information to be securely identified as boat-burials. From these fifteen sites seventeen boat-burials are included in the analysis. The analysis compares size, frequency of discovery, number of human occupants, animal remains and grave-goods from the boat-burials. Despite the fact that the burials from these regions are for the most part very similar to their counterparts, they do show signs of distinct regional characteristics.